Lymphocyte Levels in Predicting the Outcome of COVID-19 Patient: A Prognostic Study from Single Center in Indonesia - Amin, Chris Alberto; Liana, Phey; Ahmad, Zen; Hidayat, Rachmat; Sari, Nurmalia Purnama; Afifah, Astari Rahayu; Hilda, Fadhilatul (Journal of Nepal Health Research Council, 2021)
Background: Several laboratory parameters have been linked to Corona Virus Disease 2019 (COVID-19), with lymphocytes being one of the most important. Lymphopenia is frequently linked to a worsening of clinical symptoms and an increased risk of death in COVID-19. This study aimed to determine the role of lymphocyte levels in predicting COVID-19 patient mortality. Methods: This is a prognostic study that is conducted from March 1 to August 31, 2020. Data from medical records and laboratory findings of COVID-19 patients were used in the study. Patient distribution and complete blood count were among the information gathered. ROC curve analysis, bivariate analysis (Chi-Square and Mann Whitney), in addition to survival analysis (Kaplan-Meier) were used to analyze the data. Results: In a total of 318 patients, 59 were non-survivors and 259 were survivors. Besides, a cut-off value of ?1460 cells/µL (P<0.05) was used for lymphocyte levels. Lymphopenia also has a 4.35-fold increase in the risk of mortality. Furthermore, the survival analysis revealed differences in the probability of survival within 30 days between COVID-19 patients with lymphopenia and those without (HR: 5.5722 (3.2509–9.5510), 95% CI; p<0.0001). A lymphocyte count of ?1460 cell/µL can increase the risk of death by fourfold.Conclusions: The findings of this study indicated a significant difference in outcome between lymphopenia and non-lymphopenia patients. Lymphopenia plays an important role in estimating COVID-19 patient mortality.Keywords: COVID-19; lymphopenia; mortality; prognosis; survival analysis